Acute Pancreatitis - The Current Concept in Ethiopathogenesis, Morphology and Complications - Shetty, B. Suresh Kumar; Naik, Ramdas; Shetty, Adithi S.; Rai, Sharadha; Menezes, Ritesh G.; Kanchan, Tanuj (IntechOpen, 2012)
None